Dibutyltin Dichloride Retards Leydig Cell Developmental Regeneration in Adult Rat Testis - Huang, Xiande; Ma, Taoye; Yin, Yongsheng (Frontiers in Pharmacology, 2018)
Dibutyltin dichloride (DBTCl), widely used as plastic stabilizer, can cause comprehensive toxicity. The objective of the present study is to investigate the effects of DBTCl on rat Leydig cell regeneration and to characterize the underlying mechanism. Adult male Sprague Dawley rats were randomly assigned into four groups and gavaged with saline (control) or 5, 10 or 20 mg/kg/day of DBTCl for 10 consecutive days. At the end of DBTCl treatment, all rats received a single intraperitoneal injection (i.p.) of 75 mg/kg ethane dimethane sulfonate (EDS) to eliminate all of the adult Leydig cells and to induce Leydig cell regeneration. Leydig cell regeneration was evaluated by measuring serum testosterone, luteinizing hormone, and follicle-stimulating hormone levels on days 7, 35, and 56 post-EDS. Leydig cell gene and protein expression levels, as well as cell morphology and cell counts were also carried out on day 56 post-EDS. We found that DBTCl significantly reduced serum testosterone levels on days 35 and 56 post-EDS, but increased serum luteinizing hormone (LH) and follicle-stimulating hormone (FSH) levels on day 56 at ≥5 mg/kg/day. The mRNA and protein levels of Leydig (Lhcgr, Scarb1, Star, Cyp11a1, Hsd17b3 and Hsd11b1) and Sertoli cells (Fshr, Amh, and Sox9) were significantly downregulated in the DBTCl-treated testes compared to the control. Immunohistochemical staining showed that DBTCl-treatment caused fewer regenerated Leydig cells and impaired Sertoli cell development and function in the testis on day 56 post-EDS. In conclusion, the present study demonstrates that a short-term DBTCl exposure retards Leydig cell developmental regeneration via downregulating steroidogenesis-related enzymes at the gene and protein levels, inhibiting Leydig cell proliferation and impairing Sertoli cell function and development.